Age-related histopathological lesions in the Mongolian gerbil ventral prostate as a good model for studies of spontaneous hormone-related disorders - Campos, Silvana Gisele Pegorin; Zanetoni, Cristiani; Scarano, Wellerson Rodrigo; Vilamaior, Patricia Simone Leite [UNESP]; Taboga, Sebastiao Roberto [UNESP] (Blackwell Publishing, 2008)
The Meriones unguiculatus (Mongolian) gerbil has demonstrated significant prostatic responses to hormonal treatments, and to drugs against human prostatic hyperplasia Spontaneous neoplasia develops in the older animals. Thirty gerbils (age 18 months) were divided into non-affected and prostatic lesion bearers and the prostate lesions were evaluated morphologically, immunohistochemically and quantitatively. The most frequent changes were in epithelial sites and, namely prostatic intraepithelial neoplasias, microinvasive carcinomas and adenocarcinomas. In the stromal compartment, cellular hyperplasia, when verified, was always associated with the sites of anomalous epithelium. Additionally, larger deposition of collagen fibrils, generating stromal fibrosis, was found in all the old gerbils analysed. The quantitative analysis showed that prostatic tissue proportions differed in altered areas, being specific for each lesion type. Isolated nuclear and nucleolar parameters were not effective in diagnosing the malign potential of lesions. However, the cellular proliferation and death indexes indicated larger cellular turnover in invasive lesions such as carcinomas. With these analyses, it could be verified that old gerbils present high propensity to develop spontaneous prostate changes and this may aid in a better understanding of the biological behaviour of human prostate cancer.
Keywords: ageing; cellular proliferation; gerbil; prostate cancer; prostatic intraepithelial neoplasia; ventral prostate